2020
DOI: 10.3390/jcm9061614
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Usage Data from a Self-Guided App-Based Virtual Reality Cognitive Behavior Therapy for Acrophobia: A Randomized Controlled Trial

Abstract: This study examined user engagement with ZeroPhobia, a self-guided app-based virtual reality (VR) Cognitive Behavior Therapy for acrophobia symptoms using cardboard VR viewers. Dutch acrophobic adults (n = 96) completed assessments at baseline and immediately following treatment. Primary outcome measures were the Acrophobia Questionnaire (AQ) and the Igroup Presence Questionnaire (IPQ). Usage data consisted of number of VR sessions practiced, practice time, and fear ratings directly after practicing. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…According to the encouraging benefits of VR, there is an ongoing body of research to explore its treatment capabilities. Recently, ten patients aged (21)(22)(23)(24)(25) years participated in a study that integrated VR with Kinect to evaluate the efficacy of VR for reducing acrophobia [23]. The virtual system used in the study was a simulation game called "Acrophobia Simulator".…”
Section: A Vr For Acrophobia Treatmentmentioning
confidence: 99%
“…According to the encouraging benefits of VR, there is an ongoing body of research to explore its treatment capabilities. Recently, ten patients aged (21)(22)(23)(24)(25) years participated in a study that integrated VR with Kinect to evaluate the efficacy of VR for reducing acrophobia [23]. The virtual system used in the study was a simulation game called "Acrophobia Simulator".…”
Section: A Vr For Acrophobia Treatmentmentioning
confidence: 99%
“…Although therapeutically simple, such virtual scenarios may nonetheless carry substantial practical benefits: VR exposure therapy for phobias for example ( Botella et al, 2017 ), solves many of the logistic issues in providing exposure therapy by enabling exposure to otherwise unavailable stimuli ( Lindner et al, 2017 , Lindner et al, 2020a ), allows tailoring of stimuli ( Rizzo et al, 2010 ) and makes it fully controllable. VR exposure therapy has been shown to be efficacious by numerous meta-analyses ( Carl et al, 2018 ; Fodor et al, 2018 ; Wechsler et al, 2019 ) and new research has demonstrated efficacy also in an automated, gamified format ( Donker et al, 2019 , Donker et al, 2020 ; Freeman et al, 2018 ; Lindner et al, 2020b ; Miloff et al, 2019 ) that makes more extensive use of the capabilities inherent to the technology, e.g. by featuring an embodied virtual therapist ( Miloff et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Three high-quality randomized trials have been published recently, featuring three different applications: two on acrophobia with comparison against waiting-list (Donker et al 2019;Freeman et al 2018) and one on spider phobia examining non-inferiority against gold-standard in vivo exposure (Miloff et al 2019). Findings from the later spider phobia trial have since been replicated in a single-subject trial with simulated real-world conditions (Lindner et al 2020b) and valuable usage data from one of the acrophobia trials has also been reported (Donker et al 2020). A qualitative study on the experience of undergoing automated VR exposure therapy for spider phobia has also been published (Lindner et al 2020c).…”
Section: Automated Treatmentsmentioning
confidence: 99%
“…While research has begun to collect and analyze user engagement metrics and selfreported data from self-guided VR interventions (Donker et al 2020), there has been surprisingly little research on data that offers deeper insight. The entire concept of (HMD) VR relies on continuous head rotation tracking, making rotation a suitable user interface through the use of a crosshair that fixates eye gaze and synchronizes it (at least to same degree) with head rotation.…”
Section: Full Immersion Through Innovative User Interfaces and Makingmentioning
confidence: 99%